PENINGKATAN AKTIVITAS BELAJAR MENGGUNAKAN MODEL PROBLEM BASED LEARNING DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Syah, Subhan (Jurnal Kajian Pembelajaran dan Keilmuan, 2022)
This classroom action research aims to describe the increase in student learning activities using the Problem Based Learning model. This research is collaborative with colleagues. The number of subjects used in this study were 20 students who came from class V Elementary School 25 East Pontianak. The research subjects consisted of 11 men and 9 women. In this study, direct observation technique was used in this study with the help of learning activity observation sheets, planning observation sheets and implementation observation sheets. The results of observations on the learning activities of class V students using the Problem Based Learning model in the first cycle obtained a percentage of 54%. The results of the observation of student learning activities in the second cycle obtained a percentage of 96%. The conclusion of this study is that the use of the Problem Based Learning model in class V of Public Elementary School 25 East Pontianak is able to increase student learning activities, namely in the first cycle of 54%, an increase of 42% to 96%.